Estimates of self-reported dietary behavior related to oral health among adolescents according to the type of food - Regiane Cristina do AMARAL; Luiz Felipe SCABAR; Betzabeth SLATER; Paulo FRAZÃO (University of São Paulo, 2014)
Objective: To compare estimates of food behavior related to oral health obtained through a self-report measure and 24 hour dietary recalls (R24h). Method: We applied three R24h and one self-report measure in 87 adolescents. The estimates for eleven food items were compared at individual and group levels. Results: No significant differences in mean values were found for ice cream, vegetables and biscuits without filling. For the remaining items, the values reported by the adolescents were higher than the values estimated by R24h. The percentage of adolescents who reported intake frequency of 1 or more times/ day was higher than the value obtained through R24h for all food items except soft drinks. The highest values of crude agreement between the instruments, individually, were found in the biscuits without filling (75.9%) and ice cream (72.4%). Conclusion: The results suggest that adolescents tend to report a degree of exposure to the food items larger than what they actually experience in their daily lives.